Anemia and Low Testosterone Associated with Male Type 2 Diabetic Patients: Samal Hakeem Kareem AL-Jaff, Majid Ahmed Naseif AL-Bayati, Noor Adil Abood - AL-Jaff, Samal Hakeem Kareem (The Iraqi Journal of Veterinary Medicine, 2010)
Diabetes Type 2 is associated with low testosterone levels in men, The mechanism of which is unclear .Thus the aim of this study was to estimate the incidence of low testosterone in T2D patients men ⁄ and with aging ,and the possibility of anemia in these patients and the anemia accompanied the T2D cases is due to T2D itself or by the effect of low testosterone. Present work was studied two male groups with different age first, group A age (31-40) years , 60 person 30control & 30 T2D patients (3 persons for each age),second, group B age (41-50) years ,60 person ,30 control & 30 patients (3 persons for each age). Blood was taken from these groups and sugar, PCV, Hb and Testosterone levels were measured comparing with control of each and between two groups and in each data, the mean data of the same age has been taken. Present results showes that male T2D patients have significantly low T. levels P≤0.05 and significantly P≤0.05 low Hb and PCV comparing with sugar level which was significantly high P≤0.05 ,and group B (41-50) age have the lowest T. level ,PCV and Hb with higher sugar levels. We concluded that anemia and low T. level associated with T2D , and the effect of low testosterone on anemia is little .Our data shows that low T. level and anemia increased with age T2D groups in both group A&B , and in control groups in both A&B bout it is more sever and alarming in T2D cases.